2020
DOI: 10.1093/humrep/dez295
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pregnancy and live birth rates after in vitro fertilization in women with previous Caesarean section: a retrospective cohort study

Abstract: STUDY QUESTION Does a previous Caesarean section affect reproductive outcomes, including live birth, in women after IVF or ICSI? SUMMARY ANSWER A previous Caesarean section impairs live birth rates after IVF or ICSI compared to a previous vaginal delivery. WHAT IS KNOWN ALREADY Rates of Caesarean sections are rising worldwide. Late sequelae of a Caesarean sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 29 publications
1
64
0
Order By: Relevance
“…This points to the niche as the causal factor for fluid accumulation. Pregnancy rates were also very promising in that study in which 40.2% of subjects had failed previous IVF therapy; at 2 years of follow-up, 52.0% conceived naturally with a median time to pregnancy of 3.0 months after discontinuation of contraceptives ( Vissers et al , 2020 ). Two other cohort studies on laparoscopic niche repair in 22 and 38 subfertile patients reported high pregnancy rates (55.6% and 44.0%, respectively) in most patients after more than 1-year follow-up ( Tanimura et al , 2015 ; Donnez et al , 2017 ).…”
Section: Detrimental Environment For Sperm Penetration and Implantatimentioning
confidence: 93%
See 4 more Smart Citations
“…This points to the niche as the causal factor for fluid accumulation. Pregnancy rates were also very promising in that study in which 40.2% of subjects had failed previous IVF therapy; at 2 years of follow-up, 52.0% conceived naturally with a median time to pregnancy of 3.0 months after discontinuation of contraceptives ( Vissers et al , 2020 ). Two other cohort studies on laparoscopic niche repair in 22 and 38 subfertile patients reported high pregnancy rates (55.6% and 44.0%, respectively) in most patients after more than 1-year follow-up ( Tanimura et al , 2015 ; Donnez et al , 2017 ).…”
Section: Detrimental Environment For Sperm Penetration and Implantatimentioning
confidence: 93%
“…In conclusion, accumulation of fluid is seen in approximately 42% of patients with a large niche ( Vissers et al , 2020 ). This may impair pregnancy outcomes due to reduced implantation yet may also be embryotoxic.…”
Section: Detrimental Environment For Sperm Penetration and Implantatimentioning
confidence: 94%
See 3 more Smart Citations